Transforming Attitude Towards Security and Defense: The European Union's Strategic Response to the 2022 Russian Invasion of Ukraine - Zieliński, Tadeusz (Polityka i Społeczeństwo, 2024)
The 2022 Russian invasion of Ukraine has led to a significant reassessment of the European Union's security and defense policies, shifting from a historical reliance on soft power to autonomous defense strategy. This article aims to analyze the EU's adjustments in response to the conflict, focusing on the evolution of its security and defense policies and their implications for future EU-Ukraine relations. Employing qualitative analysis of policy documents, official statements, and scholarly articles, the study examines the EU's sanctions, military support, and strategic reorientation. The findings reveal that the EU has implemented comprehensive economic sanctions against Russia, provided unprecedented military and humanitarian aid to Ukraine, and reoriented its defense policies towards deterrence and territorial defense. The study also identifies significant internal disparities among EU member states regarding strategic priorities. Enhanced coordination with NATO, increased defense spending, and investments in advanced military technologies are key aspects of the EU's strategic shift. The potential long-term changes in EU security policy point towards greater strategic autonomy and an enhanced global security role. The future of EU-Ukraine relations will be shaped by these strategic shifts, with scenarios ranging from deepened integration and reconstruction support to continued humanitarian and diplomatic efforts under various conflict outcomes.